Self‐regulation of older drivers with cognitive impairment: A systematic review. (30th June 2013) - Devlin, Anna; McGillivray, Jane A
<x xml:space="preserve">Abstract</x> Background Cognitive decline contributes significantly to the safety risk of older drivers. Some drivers may be able to compensate for the increased crash risk by avoiding complex driving situations or restricting their driving. Objective and Method A comprehensive English‐language systematic review was conducted to determine the level of evidence for older adult drivers with cognitive impairment engaging in self‐regulation. Results Twelve studies were included in the review. The majority of studies investigated driver avoidance, followed by driver restriction. Few studies ascertained the reasons for changing driving behaviour. Conclusions The evidence supports the view that drivers with cognitive impairment do restrict their driving and avoid complex driving situations. However, it remains to be determined whether the drivers who engage in self‐regulation have insight into their own driving abilities or whether external factors result in self‐regulation of driving behaviour.